The Bunkie Test - Ronai, P. (Strength and Conditioning Journal, 2015)
The technique for administering the bunkie test, which is an assessment of muscle endurance, length, and function of core stabilizing muscles, is described. This test can help strength and conditioning professionals select exercises and improve their client's core stability.